Real-time calibration technology of non-contact material surface temperature based on laser and multispectral inversion - Zhu, Zhaohui; Zhan, Chunlian; Gan, Han (Journal of physics. Conference series, 2025)
Radiation temperature measurement is a non-contact temperature measurement method based on the thermal radiation characteristics of objects. Obtaining the true temperature of the target by using the radiation temperature measurement method can not only ensure the safety and reliability of the testing process, but also significantly improve the temperature measurement accuracy. However, this method is greatly affected by factors such as the environment and test conditions. To address this issue, this paper proposes a radiation temperature measurement method based on laser modulation to calibrate parameters such as emissivity, reflectance, and gas transmittance of the material surface in real time, and combines the radiation temperature field inversion algorithm to obtain the true temperature of the material surface. Research shows that under the modulation of CO 2 lasers, the corresponding emissivity values can be obtained in real time according to the changes in surface temperature, and then the real-time temperature values can be calculated through the temperature inversion algorithm.